Building effective local government in New Zealand: creatures of statute or expressions of local democracy? - Mckinlay, Peter (2016)
This research note - as a basis of an ongoing wider assessment - considers New Zealand's recent experience of the relationship between central government and the local government sector under successive National party led minority governments. It is essentially a story of successive endeavours by the central government to reshape local government in terms of a core services efficiency understanding of the role of local government. It raises important questions about whether a focus on efficiency is consistent with, or inherently in conflict with, understandings of local voice and representation. - Reproduced.
Keywords: Local government - New Zealand; Local government